Fibroma on Auricular Pavilion in a Mare - Diagnosis and Surgical Treatment - Rocha Silva, Aline; Carlos de Sousa, Marilaine; Guimarães Santana Freire, Natália; Souza Moreira, Nadyne; Cachineiro Rodrigues Dias, Domingos; Velozo Leal, Paula; Gouvea Teixeira, Luisa (Acta Scientiae Veterinariae, 2024)
Background: Fibroma is an uncommon benign neoplasm in horses, locally expansive and originating from dermal or subcutaneous fibroblasts. They are mainly observed in adult horses without predisposition by sex or breed and their cause is unknown. Lesions are generally solitary, well circumscribed and located in the dermis or subcutaneous tissue. The aim of this work is to report a case of fibroma in a 30-month-old mare, describing the surgical and postoperative treatment, histopathological examination, as well as the results obtained. Case: A mixed breed mare was seen at 30 months of age, weighing 370 kg and presenting an increase in volume with a nodular appearance located at the base of the caudal edge of the left auricular pavilion. It was reported that this increase in volume had progressed over 4 months with rapid growth in the last 30 days, becoming peduncular and with local itching for 15 days. On physical examination, the animal showed changes only in the integumentary system, with small aural plaques also being observed in the right and left ear pinna. The blood count revealed homochromic normocytic anemia, and the coproparasitological examination revealed 1,350 eggs from the Trichostrongyloidea family, indicating verminosis. Ivermectin [0.2 mg/kg, orally] was administered in 2 doses, 14 days apart. After this treatment, the patient did not present anemia and no helminth eggs were observed during coproparasitological examination. After this, the animal underwent surgery where total excision of the neoplasm was performed. There were no postoperative complications or recurrences and the patient was followed for 18 months, showing full development of her athletic activities. The nodule was sent to the veterinary pathology laboratory for histopathological analysis. Macroscopically it measured 4.5 x 3.5 x 3.5 cm, was pedunculated, circumscribed, ulcerated, reddish and firm elastic. When cut, it appeared compact, multilobular and white. Microscopic findings included an abnormal proliferation of fibroblasts that produced excess collagen. The cells were fusiform, with indistinct cell boundaries, elongated and hyperchromatic nuclei with non-evident nucleoli. In addition, there was inflammation, areas of necrosis and discontinuity of the epidermis. Masson’s trichrome staining showed proliferation of spindle cells with bluish cytoplasm and areas of edema between the cells. Discussion: The neoplasm observed at the base of the left ear pinna of the mare mentioned in this report could be equine sarcoid, due to the macroscopic characteristics and greater prevalence in the equine population, this being the first suspicion. Fibromas and sarcoids are similar macroscopically and can be confused, however, they are differing in their essential histological characteristics. Equine sarcoid is distinguished by having a hyperplastic and hyperkeratotic epithelial component with typical extensions (retepegs) in immature dermal fibroblasts, often with mitotic figures, in a spiral fibro cellular mass. Fibromas, on the other hand, generally do not have an epithelial component and have fibroblasts with a low mitotic index, with intertwined collagen fibers and random orientation as described in the present report. The surgical procedure was performed as indicated for cases of fibroma, without postoperative complications, being successful in treating the patient and preventing recurrence. The histopathological examination was essential for the correct diagnosis, to support therapy and establish the patient’s good prognosis. Keywords: equine, surgical excision, fibroblasts, histopathological examination, neoplasia. Título: Fibroma no pavilhão auricular em uma égua - Diagnóstico e tratamento cirúrgico Descritores: equino, excisão cirúrgica, fibroblastos, exame histopatológico, neoplasia.